Halobacteriovorax isolated from the Adriatic Sea to challenge Salmonella - Pieralisi, Silvia; Hattab, Jasmine; Mosca, Francesco; Angelico, Gabriele; Lanci, Laura; Ottaviani, Donatella; Rocchegiani, Elena; Giorgio Tiscar, Pietro (Italian Journal of Food Science, 2024)
In the present study, we searched Halobacteriovorax strain preying upon Salmonella from the seawater of the Adriatic Sea. The Halobacteriovorax strain, named M7, was identified using 16S rRNA analysis. The M7 strain predation efficiency was tested against different Salmonella and non-Salmonella strains, all isolated from food matrices obtained from the Adriatic Sea. Finally, the M7 strain was exposed to Salmonella enterica subsp. enterica serovar Napoli in challenge tests to evaluate the killing of this specific prey over time. Double -layer agar plating technique was used to enumerate Halobacteriovorax and to evaluate its host specificity and predation efficiency. In the 103 predator/103 prey challenge test, M7 caused a decrease of Salmonella by about 2 log at 24 h compared to the control. In the 107 predator/104 prey challenge test, M7 caused a decrease of Salmonella by about 5 log at 24 h compared to the control, and good levels of decrease were obtained even at shorter times. Halobacteriovorax strains active against Salmonella are rarely present in the Adriatic Sea, Italy seawater. However, the isolate M7 showed high predatory efficiency towards a wide range of Salmonella strains. The presence of Salmonella in bivalves affects food safety since current decontamination processes are not always effective. M7 may represent a potential candidate for reducing and controlling Salmonella contamination in bivalves from harvesting to trade.